A prospective study of neurodevelopmental trends between 3 and 24 months in normocephalic infants with prenatal Zika virus exposure: Evidence of emerging communication delays in the NATZIG cohort. (December 2021) - Key, Alexandra P.; Negrini, Silvia F.B. de Moura; Caldas, Carla A.C. Tanuri; Teixeira, Sara Reis; Anastasio, Adriana R.T.; Cavalcante, Juliana; Mussi-Pinhata, Marisa M.; Hood, Linda J.
Summary: Developmental trends between 3 and 24 months were assessed in 194 normocephalic infants with prenatal Zika virus exposure. Bayley Scales of Infant and Toddler Development Screening Test–3rd Edition cognitive scores remained in the typical range. Communication skills developed at a slower rate suggesting that neurodevelopmental delays may emerge at older ages. Highlights: The study investigated neurodevelopment in 194 normocephalic infants prenatally exposed to Zika virus. Bayley Scales of Infant and Toddler Development Screening Test administered repeatedly between 3 and 24 months. Communication skills develop at a slower rate than general cognitive function. Regular follow-up is needed to identify risk for developmental disabilities.